2008
DOI: 10.2147/cia.s1957
|View full text |Cite
|
Sign up to set email alerts
|

Model of human aging: Recent findings on Werner’s and Hutchinson-Gilford progeria syndromes

Abstract: The molecular mechanisms involved in human aging are complicated. Two progeria syndromes, Werner’s syndrome (WS) and Hutchinson-Gilford progeria syndrome (HGPS), characterized by clinical features mimicking physiological aging at an early age, provide insights into the mechanisms of natural aging. Based on recent findings on WS and HGPS, we suggest a model of human aging. Human aging can be triggered by two main mechanisms, telomere shortening and DNA damage. In telomere-dependent aging, telomere shortening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 183 publications
(304 reference statements)
0
46
0
Order By: Relevance
“…The classic example of progeroid syndrome Werner syndrome is an adult progeria caused by a mutation of the gene encoding the RecQ helicase, with the appearance of visible signs of aging such as skeletal changes and graying of hair early age and premature death [33,34]. Syndrome Hutchinson-Gilford progeriais a child progeria, a rare genetic disorder first described by Jonathan Hutchinson in 1886 and Hastings Gilford in 1897.…”
Section: Genetic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic example of progeroid syndrome Werner syndrome is an adult progeria caused by a mutation of the gene encoding the RecQ helicase, with the appearance of visible signs of aging such as skeletal changes and graying of hair early age and premature death [33,34]. Syndrome Hutchinson-Gilford progeriais a child progeria, a rare genetic disorder first described by Jonathan Hutchinson in 1886 and Hastings Gilford in 1897.…”
Section: Genetic Mechanismsmentioning
confidence: 99%
“…It is characterized by premature aging phenotype with involvement of skin, bones, heart and blood vessels. Patients have the appearance of "plucked bird" and die prematurely from cardiovascular disease in the second decade of life [33,35,36].…”
Section: Genetic Mechanismsmentioning
confidence: 99%
“…All these syndrome, which are characterized by elevated genomic instability. 70,71 We recently demonstrated that loss of WRN induces accumulation of chromosome gaps and breaks specifically at CFS even under unperturbed conditions. 65 In addition, exposure of cells to low doses of aphidicolin leads to extensive relocalization of WRN to nuclear foci in replicating cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The cells of these patients are prone to cellular senescence and neoplastic transformation and have an elevated genomic instability [7, 8] and sensibility to DNA damage induced by oxidative stress [4, 9]. …”
Section: Introductionmentioning
confidence: 99%